Karakteristik dan Pengembangan Pelayanan Pendidikan Islam Anak Tunadaksa - Seviarica, Hilda Putri; Akhmad, Fandi; Berliyana, Adhe Sukma; Atmojo, Sugeng Tri; Fauzi, Robi (Lembaga Yasin AlSys, 2021)
This study aims to characterize and develop Islamic education services for children with disabilities. The type of research used in this research is literature research, to discuss the characteristics and development of Islamic education services for children with disabilities. Data collection techniques use documentation techniques by collecting data through documents, data sources that are inanimate, such as notes, letters, and photos. The results showed that there are several characteristics of children with physical disabilities, including: social or emotional characteristics, sensory disorders, motor disorders, speaking skills, academic characteristics, physical characteristics. Children with special needs who experience damage or lose their physical members, the process of developing Islamic religious education materials in providing materials or teaching methods is almost the same as children with visual impairments and visual impairments. Meanwhile, the model for developing children with disabilities is through the school environment, family environment, and community environment.